2008
DOI: 10.5863/1551-6776-13.4.233
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study Evaluating the Effectiveness of an Asthma Clinical Pathway in Pediatric Inpatient Practice

Abstract: OBJECTIVE To determine if the asthma clinical pathway implemented at Wolfson Children's Hospital reduces the length of hospital stay. To determine if pathway use affected the use of asthma education, the use of appropriate discharge medications based on asthma classification, and readmission rates. METHODS A list of patients aged 2 to 18 years discharged from Wolfson Children's Hospital between September 1, 2004 and August 31, 2006 with the diagnosis of asthma was generated. Medical records of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Several studies have demonstrated that pathways are effective in improving quality of care and health outcomes for children hospitalized with asthma (3)(4)(5)(6)(7)(8)(9)12). However, none, to our knowledge, have detailed the pathway implementation process across a large, diverse group of hospital settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that pathways are effective in improving quality of care and health outcomes for children hospitalized with asthma (3)(4)(5)(6)(7)(8)(9)12). However, none, to our knowledge, have detailed the pathway implementation process across a large, diverse group of hospital settings.…”
Section: Discussionmentioning
confidence: 99%
“…Pathways promote standardization of care, with the aim of improving care quality and decreasing unnecessary healthcare utilization. They have been shown to improve care for children hospitalized with asthma, including increasing use of recommended medications, and decreasing length of hospital stay, healthcare costs, hospital readmissions, and healthcare disparities (3)(4)(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…The estimate of its prevalence is variable depending on the criteria used (symptomatic forms or not) and the tools used (none: clinical diagnosis only, monofilament, instrumental quantitative exploration of sensitivity or electroneuromyogram). It is estimated that it reaches about 30% of diabetic subjects at the time of diagnosis [1] with extremes ranging from 8 to 54% in type 1 diabetes and 13 to 46% in type 2 diabetes [2].…”
Section: Introductionmentioning
confidence: 99%
“…Pathways have been shown to improve quality of care for children who are hospitalized with asthma by increasing the use of recommended medications such as bronchodilators and corticosteroids, reducing use of antibiotics, decreasing LOS and associated health care costs, and improving health care disparities. [9][10][11][12][13][14] This previous research has primarily consisted of single-center studies in large, tertiary children's hospitals 9 ; however, ,30% of childhood hospitalizations in the United States occur in these settings. 15 Thus, the purpose in our initiative was to improve inpatient asthma care for children by implementing pathways in a diverse, national sample of hospitals.…”
mentioning
confidence: 99%